2013
DOI: 10.2478/agri-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilization on ß-D-Glucan Content in Oat Grain (Avena Sativa L.)

Abstract: β-D-glucan is a soluble component of dietary fibre localised in the cell walls of cereal grains, especially oat and barley. This homopolysaccharide presents a wide spectrum of health-beneficial effects in human beings, and its higher concentration in oats makes it an essential component for human nutrition. Genetic and environmental factors influence the content of β-D-glucan. Four oat varieties (two naked and two hulled) were grown in experimental fields at Vígľaš-Pstruša (Central Slovakia) in two consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Previous data also showed that both oat genotype and agronomic practises, as seeding season and rotation, can be important determinants of the variability of protein and b-glucan (Redaelli et al 2009). In this context, our data confirm the observations by Havrlentová et al (2013), who reported that yield is less sensitive to nitrogen fertilization in husked than in naked oats, whereas increasing nitrogen doses have a positive effect on b-glucan content, especially in husked genotypes. In the present study, where different oat genotypes and agronomical factors were tested in two consecutive experiments, the statistical evaluation of the differences in grain nutritional quality was synthesized graphically by box-plots, in which the four years were clearly differentiated, and a larger variability for b-glucan content as compared to proteins was observed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous data also showed that both oat genotype and agronomic practises, as seeding season and rotation, can be important determinants of the variability of protein and b-glucan (Redaelli et al 2009). In this context, our data confirm the observations by Havrlentová et al (2013), who reported that yield is less sensitive to nitrogen fertilization in husked than in naked oats, whereas increasing nitrogen doses have a positive effect on b-glucan content, especially in husked genotypes. In the present study, where different oat genotypes and agronomical factors were tested in two consecutive experiments, the statistical evaluation of the differences in grain nutritional quality was synthesized graphically by box-plots, in which the four years were clearly differentiated, and a larger variability for b-glucan content as compared to proteins was observed.…”
Section: Discussionsupporting
confidence: 82%
“…The role of crop rotation and environment on grain bioactive components in a group of naked oats was also examined (Redaelli et al 2009). Finally, the effect of fertilization on the content of b-glucan in naked oats was explored (Havrlentová et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Differences among nitrogen application treatments in the amount of b-glucan were significant (p < 0.05) only for husked oat genotype. Similarly, Havrlentova et al (2013) observed that b-glucan content of husked oat was significantly affected by nitrogen fertilisation, while content of naked oat was affected only by genotype. Fan et al (2009) did not observe significant differences in content of b-glucan among nitrogen treatments.…”
Section: Discussionmentioning
confidence: 79%
“…Temperatures and precipitation sum are the main climatic factors influencing oat growth and development. Havrlentova et al (2013) found that the growing year did not significantly affect b-glucan concentration in grains. Our research showed significant (p < 0.05) effect of growing season on b-glucan content of husked and naked oats.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation